MATEC Web of Conferences - Aldoshina; Yugay; Kaliaskarov; Esenjolov; Nesipova (2018)
The Article describes the construction design and experimental results of the Solar Simulator, based on powerful LEDs with different radiation spectrum. There was established that the block from 25 light-emitting diodes provides radiation intensity sufficient for carrying-out of AM1.5G standard requirements. Fine tuning of the resultant spectrum and the required illumination for all radiation spectral components were obtained through light-emitting diodes current control.